1973
DOI: 10.1136/pgmj.49.567.29
|View full text |Cite
|
Sign up to set email alerts
|

Thiazides and hypokalaemia in diabetic ketoacidosis

Abstract: Summary In a series of forty-one episodes of diabetic coma or pre-coma, three patients had plasma potassium values of less than 3.0 mEq/l. All three had been taking thiazide diuretics with only one receiving oral potassium supplements. None was previously known to be diabetic, representing 18% of the new diabetics in the series. The mean plasma potassium for the other new diabetics was 4·7 ± 0·2 mEq/l. These findings emphasize that adequate potassium supplements should be given with thiazide diu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Weidmann et al demonstrated a 10% fall in total body sodium, back to normal levels, on diuretics with an improvement in mean blood pressure from 165/93 to 145/82 mmHg [41]. There are, however, a number of disadvantages (Table 3): thiazides have been shown to worsen glucose tolerance in non-insulin-requiring patients, probably because of both hypokalaemia and a further separate action [90,91]. Apart from their considerable side-effects in any subject, recent evidence from the Medical Research Council trial of mild hypertension suggests that they are also associated with a significant incidence of impotence [86], rendering them less than ideal for many male patients.…”
Section: Diureticsmentioning
confidence: 99%
“…Weidmann et al demonstrated a 10% fall in total body sodium, back to normal levels, on diuretics with an improvement in mean blood pressure from 165/93 to 145/82 mmHg [41]. There are, however, a number of disadvantages (Table 3): thiazides have been shown to worsen glucose tolerance in non-insulin-requiring patients, probably because of both hypokalaemia and a further separate action [90,91]. Apart from their considerable side-effects in any subject, recent evidence from the Medical Research Council trial of mild hypertension suggests that they are also associated with a significant incidence of impotence [86], rendering them less than ideal for many male patients.…”
Section: Diureticsmentioning
confidence: 99%
“…It tends to be associated with severe ketoacidosis and/ or hyperglycaemia and its presence adversely affects the rate at which the metabolic changes can be corrected. (Alberti and Hockaday 1973). Its presence should always be sought for and in the gravely ill, assumed.…”
Section: Causesmentioning
confidence: 98%
“…There is evidence to suggest that irrespective of the degree of ketoacidosis, satisfactory response can be obtained by an initial dose of 20 i.u. followed at hourly intervals by a further 5 ‐ 10 units (Alberti et al , 1973). A similar regimen in which the dose of insulin is related to body weight has been used in children (Moseley 1975).…”
Section: Insulinmentioning
confidence: 99%
See 1 more Smart Citation